1991
DOI: 10.1122/1.550167
|View full text |Cite
|
Sign up to set email alerts
|

Time‐dependent behavior and wall slip in concentrated shear thickening dispersions

Abstract: SynopsisThe viscosity of concentrated shear thickening dispersions was measured as a function of shear rate, Couette cylinder size, and time. The level of the low shear rate viscosity, which was found to be independent of system size and time, could bc predicted by the equation of Frankel and Acrivos. At shear rates above the critical shear rate for shear thickening in highly concentrated (#> 0.57) dispersions of monodispcrse particles strong viscosity instabilities were detected, together with a dependence on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
56
0

Year Published

1992
1992
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(63 citation statements)
references
References 40 publications
7
56
0
Order By: Relevance
“…These clusters can span the whole gap and give rise to flow blockage and higher values of G'. In another study (22) we showed that in steady shear flow the presence of large clusters and plug-flow in the gap could be visualized using a photographic technique.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These clusters can span the whole gap and give rise to flow blockage and higher values of G'. In another study (22) we showed that in steady shear flow the presence of large clusters and plug-flow in the gap could be visualized using a photographic technique.…”
Section: Discussionmentioning
confidence: 99%
“…Measurements were made as quickly as possible. This means that a value for the torque at a (22). After the measuring system was filled, with care being taken not to include air in the system, the system was fitted into the rheometer.…”
Section: Steady Shear Rheologymentioning
confidence: 99%
See 1 more Smart Citation
“…Some experiments on real suspensions suggest that the shear-thickening regime is again followed by a shear-thinning region [1], [14]. On the contrary, it can be argued that in experiments on real suspensions, the influence of the experimental setup and additional forces between the particles cannot be absolutely excluded in most cases [15], [17], [18], [19]. Also in our simulations we see a continued increase of ν app to the highest-shear rates allowed by the methods we used [20] in contrast to comparable simulations that resemble more the experimental setup of real viscometers [21], [22], [23].…”
mentioning
confidence: 95%
“…For ϕ > ϕ c , a sudden increase in ν app ðγ : Þ can be observed. In the literature, values for ϕ c vary with suspension type and particle size distribution between 0.52 ≤ ϕ c ≤ 0.575 [13], [14], [15]. In the present work, we concentrate on 2D suspensions at global volume fractions ϕ ¼ 0.3 and ϕ ¼ 0.5, in which the local ϕðxÞ was apparently well below a critical ϕ ð2DÞ c not known to us.…”
mentioning
confidence: 99%